PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH SISWA PADA MATERI PERUBAHAN LINGKUNGAN - Cicilia Angelina Priska; Yokhebed, Yokhebed (Journal of Biology Learning, 2024)
This research aims to determine the application of problem-based learning to improve problem-solving skills in environmental change material. The type of research used is classroom action, which consists of 2 cycles. Each cycle consists of planning, action, observation, and reflection. The subjects in this research were 30 students in class X MIPA 1 SMA Negeri 3 Bengkayang. The research instrument used was a problem-solving skills observation sheet. The results showed that problem-solving skills increased from quite skilled to skilled. The percentage of each indicator of problem-solving skills has increased. Increase indicators identifying information gaps and the need for action by 18.97%, processing information to understand problems and making decisions by 19.83%, reaching solutions by 23.27%, and communicating decisions by 18.98%. Thus, problem-based learning can improve problem-solving skills.